Diagnosis and management of thrombotic thrombocytopenic purpura (TTP) in Australia: findings from the first 5 years of the Australian TTP/thrombotic microangiopathy registry. Issue 1 (27th January 2016) - Blombery, P.; Kivivali, L.; Pepperell, D.; McQuilten, Z.; Engelbrecht, S.; Polizzotto, M. N.; Phillips, L. E.; Wood, E.; Cohney, S.; ,
Abstract: Background: Thrombotic thrombocytopenic purpura (TTP) is a rare, life‐threatening thrombotic microangiopathy (TMA). In 2009, the Australian TTP/TMA registry was established to collect data on patients presenting with TTP/TMA throughout Australia. Aim: To summarise information on the diagnosis and management of patients with TTP collected in the first 5 years (2009–2014) of the Australian TTP registry. Methods: Registry data from June 2009 to October 2014 were reviewed. Results: Fifty‐seven patients were identified with TTP (defined as ADAMTS13 activity <10%), accounting for 72 clinical episodes. ADAMTS13 inhibitor testing was performed in nine out of 57 patients (16%), reflecting the limited availability of accredited testing facilities. Sixty‐seven out of 72 episodes were treated with therapeutic plasma exchange (PEx) using cryodepleted plasma (40% of episodes), fresh frozen plasma (36%) or a mixture (22%). Median exposure to plasma products was 55.9 L. PEx was commenced ≥2 days from stated diagnosis in 15% of episodes. Adverse reactions to PEx were common with documented allergic reactions (including life threatening) in 21% of episodes. Adjunctive immunosuppression was documented in 76% of episodes (corticosteroid 71% and rituximab 39%). Platelet transfusion was administered in 15% of episodes. Conclusions: Data from the Australian TTP/TMA registry suggest a heterogenous approach to the diagnosis and management of TTP in Australia over the assessed period. These observations highlight areas for improvement and standardisation of practice, including comprehensive diagnostic testing, more immediate access to PEx and a more uniform approach to adjunctive immunosuppression and supportive care.